2015
DOI: 10.1103/physrevlett.114.114506
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Transitions in Rotating Turbulent Rayleigh-Bénard Convection

Abstract: Sharp transitions between potentially different turbulent states are unexpected because one might think that they should be washed out by the prevailing intense fluctuations and short coherence lengths and times. Contrary to this expectation, we found a sequence of such transitions in turbulent rotating Rayleigh-Bénard convection as the rotation rate was increased. This phenomenon became most prominent at very large Rayleigh numbers up to 2 × 10 12 where the fluctuations are extremely vigorous. It was found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 35 publications
3
37
0
Order By: Relevance
“…When the parameter β also varies, the situation becomes even more complicated, as with increasing β the onset of turbulence moves to larger Ra. Moreover, with changing β, the symmetries of the flow change, influencing the Nu(Ra, Pr, β) and Re(Ra, Pr, β) dependences (see also Wei, Weiss & Ahlers (2015) on sharp transitions in RBC, caused by changes of flow symmetries).…”
Section: Discussionmentioning
confidence: 97%
“…When the parameter β also varies, the situation becomes even more complicated, as with increasing β the onset of turbulence moves to larger Ra. Moreover, with changing β, the symmetries of the flow change, influencing the Nu(Ra, Pr, β) and Re(Ra, Pr, β) dependences (see also Wei, Weiss & Ahlers (2015) on sharp transitions in RBC, caused by changes of flow symmetries).…”
Section: Discussionmentioning
confidence: 97%
“…The boundary layer is a special region of the flow, where the typical statistical characteristics of bulk turbulence are not applicable anymore [26,27]. In RBC, the boundary layer dynamics is significantly influenced by rotation [13,14] and moreover plays an important role in the transition to the enhanced heat flux state, mentioned before [8,15]. More precisely, a transition is observed from a Prandtl-Blasius boundary layer for lower rotation rates, to an Ekman boundary layer for higher rotation rates [13].…”
Section: Introductionmentioning
confidence: 92%
“…In RBC the flow is buoyancy driven: a fluid is heated from below and cooled from above. Rotating a RBC system around its vertical axis induces sharp transitions in the heat flux and boundary layer dynamics and a significant change of the dominant coherent flow structures [8,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In RBC, however, sudden transitions between different turbulent states do occur when the set-up is rotated about its vertical axis (see, e.g, [9][10][11][12][13][14][15][16][17][18][19]). These turbulent states are typically characterized by different large-scale coherent flow structures and different Table I: Several values for the critical Rossby number Ro c as found in numerical simulations [10,11,16] and experiments [11,12,[14][15][16][17]. Note that the estimated value for Ro c reported by Wei et al [17] is based on the same dataset as the one reported by Zhong and Ahlers for the case with P r = 4.38 [12,15].…”
Section: Introductionmentioning
confidence: 99%
“…These turbulent states are typically characterized by different large-scale coherent flow structures and different Table I: Several values for the critical Rossby number Ro c as found in numerical simulations [10,11,16] and experiments [11,12,[14][15][16][17]. Note that the estimated value for Ro c reported by Wei et al [17] is based on the same dataset as the one reported by Zhong and Ahlers for the case with P r = 4.38 [12,15]. For all these cases convection cells with Γ = 1 are considered.…”
Section: Introductionmentioning
confidence: 99%